Regional policies for the development of civil protection - Milić, Igor (Crisis Management Days, 2024)
The regional development of civil protection in the Republic of Croatia refers to the organization and operation of civil protection at the regional level (counties and the City of Zagreb) to ensure effective protection of citizens, property and the environment in the event of major accidents and disasters. The regional development of civil protection is crucial for strengthening society's resistance to extraordinary events, reducing the risk of disasters and ensuring a quick and coordinated response in case of crisis situations. There is an obvious need to adapt civil protection to new circumstances (climate changes, security challenges, natural risks) with the primary goal of improving the organization, role and positioning of civil protection in the national security system, as well as proactive disaster risk management. All units of regional government have adopted development plans until 2027 in accordance with the Law on the System of Strategic Planning and Development Management of the Republic of Croatia. The development plan is a medium-term act of strategic planning, which aims to determine the priority areas of development of regional self-government units. The development plans within the scope of the presented strategic goals and measures showed, among other things, the current state and development priorities of the civil protection system at the regional level. This paper aims to present a comparative analysis of regional development plans, primarily when linking development goals in accordance with the matrix of disaster risk management (planning, prevention, preparedness, response and recovery) in order to determine the direction of development. Likewise, the analysis will determine which target groups (citizens, operational forces of civil protection, citizens' associations, legal entities and/or local administration) the development goals are aimed at. The paper also aims to analyse the compliance of regional development plans with policy implementation priorities in the area of strengthening resilience to disaster risks presented in the National Development Strategy of the Republic of Croatia until 2030. Bearing in mind that the Civil Protection Development Strategy at the national level has not yet been adopted, this paper aims to identify recommendations for the development of the civil protection system at the national level as part of the legislative-planning framework, disaster risk reduction and the development of operational capacities for response to major accidents and disasters.